How to train your dragon - Cowell, Cressida (New York : Little, Brown and Company, 2010)
Chronicles the adventures and misadventures of Hiccup Horrendous Haddock III as he tries to pass the initiation test of his Viking clan by catching and training a dragon.
Originally published in the U.K. by Hodder Children$1 (Bs Books, 2003.s
Keywords: Vikings -- Fiction; Dragons -- Fiction; Heroes -- Fiction; Friendship -- Fiction; Humorous stories